Intrusion of Malware (DDoS) detection in IoT devices using Machine Learning on Cyberspace - Al Amin, Istiak; Lamiya, Salsabil; Sheikh, Noshin Anjum; Haque, S. M. Tanjimul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.